Clinical Outcome with Intravitreal Brolucizumab for Retinal Vein Occlusion (Community Based Medical Journal, 2025)
This case study tends to report that to what extent a patient with retinal vein occlusion positively responding to intravitreal injection of Brolucizumab. In this case, Brolucizumab was recommended for a 60-year-old female who primarily presented with signs of visual loss. The best corrected visual acuity recorded as CF at 3 ft (ability to count fingers at 3 feet) in her right eye and 6/12 of the left eye. The Intraocular pressure (IOP) was 18 mmHg (right) and 24 mmHg (left). The Central corneal thickness (CCT) was 530 μm (both eyes). Lental opacity was observed in both eyes. The patient achieved significant visual improvement after a one-year follow-up with brolucizumab. There were no serious adverse effects. With appropriate monitoring, brolucizumab appears to be safe and beneficial for patients with retinal vein occlusion.  CBMJ 2025 July: vol. 14 no. 02 P:198-200